Effect Of Certain Pesticides On Certain Indicators Of Rice Plants - Yunusova, L. K.; Xakulova, M.S h.; Tuychiyeva, D. S.; M. A, Abduvakhobova; Sh. K, Mirzayev; Mahkamova, M. A. (Journal of Neonatal Surgery, 2025)
The results obtained show that the activity of the catalase enzyme varies during the germination periods of rice plants, and the highest activity was detected on the 5th day of the germination period in both varieties of the harvested plant. Under the influence of pesticides Dnox and Karat, the germination rate of rice seeds decreased, that is, the germination process slowed down, and of the pesticides, Karat pesticide had a greater effect on the Iskandar variety, and Dnox pesticide had a greater effect on the Arpa-Sholi variety. On the activity of the peroxidase enzyme, which is involved in the process of lipid peroxidation during the germination, growth of the stalk and root of rice seeds, under the influence of pesticides Dnox and Karat, a decrease in the activity of the peroxidase enzyme was observed in both stalks and roots compared to the control. The activity of the catalase enzyme during the germination periods of the Arpa-Sholi (devzira) and Iskandar (alanga) varieties of rice plants was different, and the highest activity of the enzyme was determined on the 5th day of the germination period in both varieties of the harvested plants. When comparing the results of both varieties with the control indicators, it was observed that the activity of the catalase enzyme decreased under the influence of the pesticides Dnox and Carats on all studied days compared to the control.